2011
DOI: 10.1016/j.socscimed.2011.09.026
|View full text |Cite
|
Sign up to set email alerts
|

The social context of food insecurity among persons living with HIV/AIDS in rural Uganda

Abstract: HIV/AIDS and food insecurity are two of the leading causes of morbidity and mortality in sub-Saharan Africa, with each heightening the vulnerability to, and worsening the severity of, the other. Less research has focused on the social determinants of food insecurity in resource-limited settings, including social support and HIV-related stigma. In this study, we analyzed data from a cohort of 456 persons from the Uganda AIDS Rural Treatment Outcomes study, an ongoing prospective cohort of persons living with HI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
153
3
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(168 citation statements)
references
References 86 publications
(124 reference statements)
9
153
3
1
Order By: Relevance
“…Many studies in Africa and elsewhere have shown that households with HIV have a higher risk of household food insecurity [18,[27][28][29][30].However, the prevalence reported in our study by far outstrips the documented food insecurity prevalence in Kinshasa [18]. The particular context of insecurity in the region can provide an explanation; the city of Goma has been affected by civil war for many years.…”
Section: Discussioncontrasting
confidence: 52%
“…Many studies in Africa and elsewhere have shown that households with HIV have a higher risk of household food insecurity [18,[27][28][29][30].However, the prevalence reported in our study by far outstrips the documented food insecurity prevalence in Kinshasa [18]. The particular context of insecurity in the region can provide an explanation; the city of Goma has been affected by civil war for many years.…”
Section: Discussioncontrasting
confidence: 52%
“…We included demographic, clinical, health, and socioeconomic characteristics that the literature suggests may confound the relationship between receiving a nutritional intervention and adherence (2730). …”
Section: Methodsmentioning
confidence: 99%
“…However, HIV, which is concentrated among the poor, continues to be heavily stigmatized in much of sub-Saharan Africa; this stigma can prevent HIV-affected households from drawing on informal support (56). For example, in a longitudinal study among HIV-infected ARTtreated individuals in rural Uganda, both internalized HIV stigma (internalized negative views about HIV/AIDS by PLWHA) and enacted HIV stigma (experiences of discrimination related to HIV status) were strongly associated with food insecurity, which suggests that HIV stigma may contribute to the negative effects of HIV/AIDS on food security (57).…”
Section: Overview Of Conceptual Frameworkmentioning
confidence: 99%